Can Crude Oil Futures be the Good Hedging Tool for Tyre Equities? Evidence from India - Kumar, K. Abhaya; Pinto, Prakash; Hawaldar, Iqbal Thonse; Ramesh, K. G. (International Journal of Energy Economics and Policy, 2021)
This article examines the cross-hedging performance of crude futures against the tyre equity futures to hedge the tyre equity stocks. Three multivariate conditional volatility models, namely constant conditional correlation (CCC), dynamic conditional correlation (DCC) and diagonal BEKK are applied. Using the conditional covariance and variance from the MGARCH estimates, the optimal hedge ratios (OHRs) are computed. The results of this study show that the volatility spillover exists between the returns of crude oil futures and tyre equity. However, for tyre equities, the best cross hedge is tyre equity futures rather than crude futures. All the MGARCH estimates show better hedging possibility with tyre equity futures, particularly MRF futures. Keywords: CCC; Crude future; DCC; Diagonal BEKK; Tyre equity; Tyre equity futures JEL Classifications: G21; G30 DOI: https://doi.org/10.32479/ijeep.11863